Once-daily fluticasone furoate/vilanterol versus twice daily combination therapies in asthma–mixed treatment comparisons of clinical efficacy. Issue 1 (December 2016) - Svedsater, Henrik; Stynes, Gillian; Wex, Jaro; Frith, Lucy; Leather, David; Castelnuovo, Emanuela; Detry, Michelle; Berry, Scott
Abstract Background Fluticasone furoate (FF)/vilanterol (VI) is a once-daily inhaled corticosteroid (ICS)/long-acting beta2 agonist (LABA) combination. FF/VI, 92/22mcg and 184/22mcg, are approved in Europe as maintenance therapy in persistent asthma. We report data from mixed treatment comparisons (MTC) of once-daily FF/VI against established twice-daily ICS/LABA combination therapies on clinical efficacy outcomes. Methods Data from 31 parallel-group randomised controlled trials (RCTs) of ICS/LABA, of ≥8 weeks' duration in patients aged ≥12 years with asthma, identified by systematic review, were analysed using covariate-adjusted Bayesian hierarchical models for four efficacy outcomes (primary analysis). Lung function, assessed by change from baseline morning peak expiratory flow (PEF) (n  = 18 studies) and forced expiratory volume in 1 s (FEV1 ) (n  = 28), was the outcome of primary interest. Secondary objectives were assessment of relative efficacy in terms of exacerbation rates (n  = 6) and health status (n  = 7). Overall, 24 different treatment arms were included in the MTC; we report findings comparing FF/VI (92/22mcg and 184/22mcg) with fluticasone propionate/salmeterol (FP/SAL) (250/50mcg and 500/50mcg) and budesonide/formoterol (BUD/FORM) (320/9mcg and 640/18mcg). Results For PEF (margin = 12 l/min), FF/VI 92/22mcg demonstrated ≥94 % probability and FF/VI 184/22mcg >99 % probability of non-inferiority to corresponding doses of both FP/SAL and BUD/FORM. For FEV1 (margin = 100 ml), FF/VI demonstrated ≥98 % (92/22mcg) and >99 % (184/22mcg) probability of non-inferiority to both FP/SAL and BUD/FORM. Findings for exacerbations were inconclusive due to lack of data: FF/VI 92/22mcg demonstrated 74 % and 82 % probability of non-inferiority (margin = 10 %) to FP/SAL 250/50mcg and BUD/FORM 320/9mcg, respectively. For Asthma Quality of Life Questionnaire (AQLQ) score, FF/VI 92/22mcg demonstrated >99 % and 90 % probability of non-inferiority (margin = 0.25) to FP/SAL 250/50mcg and BUD/FORM 320/9mcg. Data were unavailable to assess non-inferiority of FF/VI 184/22mcg on exacerbations or AQLQ. Conclusions Both strengths of once-daily FF/VI in asthma were comparable with corresponding doses of twice-daily FP/SAL and BUD/FORM in terms of lung function in this MTC analysis. FF/VI 92/22mcg was comparable with FP/SAL and BUD/FORM on AQLQ, but exacerbation results were inconclusive. Model limitations include disconnected treatment networks and variability across studies. Our data support previous RCT findings suggesting that the efficacy of once-daily FF/VI in improving lung function and health status in asthma is comparable with twice-daily ICS/LABAs.